WORK MOTIVATION AND WORK ENVIRONMENT MODERATING OF WORK SATISFACTION ON THE EMPLOYEE PERFORMANCE DEPARTMENT OF COOPERATION AND SMEs PROVINCIAL GOVERNMENT WEST SUMATRA - Tun Huseno (Jurnal Ilmu Pemerintahan Widya Praja, 2018)
This study aims to examine the effect of job satisfaction on the employee performance of the Cooperative and SMEs of the West Sumatra Provincial Government, the influence of work motivation on the employee performance of the Cooperative and SMEs of the West Sumatra Provincial Government, the influence of the work environment on the employee performance of the Cooperative and and SMEs of the West Sumatra Provincial Government, work motivation moderates job satisfaction on the employee performance of the Cooperatives and and SMEs the West Sumatra Provincial Government, the work environment moderates the influence of job satisfaction on the employee performance of the Cooperatives and SMEs Office of the West Sumatra Provincial Government. This research was conducted at the Department of Cooperatives and SMEs of the West Sumatra Provincial Governmentwith a population of 98 people, using the Slovin formula from a population of 98 people obtained a sample of 79 people. Data collected by distributing questionnaires to all employees of the Department of Cooperatives and SMEs of the West Sumatra Provincial Government. Analysis method uses variance based least square (PLS). The results showed that there was a significant effect of job satisfaction on the employee performance of the Department Cooperatives and SMEs of the West Sumatra Provincial Government there is a significant effect of work motivation on the employee performance of the Department Cooperatives and SMEs officials of the West Sumatra Provincial Government, there is a significant influence of the work environment on the employee performance of the Department Cooperatives and SMEs of the West Sumatra Provincial Government, work motivation moderates the influence of job satisfaction on the employee performance of the Provincial Government's Cooperatives and SMEs West Sumatra, and the work environment does not moderate the influence of job satisfaction on the employee performance of the Department Cooperatives and SMEs Office of the West Sumatra Provincial Government